PENGARUH METODE PEMBELAJARAN VIRTUAL REALITY TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK NEGERI 8 PANDEGLANG - Ari Hasan Anshori; Ahsan Iradat; Ade Dini Khoiriah (Jurnal Pendidikan Nusantara, 2025)
Students' low critical thinking skills are characterized by a lack of ability to analyze, evaluate, and relate religious material to real-life contexts. Conventional methods, which still dominate classroom learning, are considered less effective in promoting higher-order thinking skills. This study aims to determine the extent to which the use of Virtual Reality technology can shape and enhance students' critical thinking skills through a more immersive and interactive understanding of religious concepts. This research uses a quantitative approach with a quasi-experimental design, specifically the posttest-only control group design. The sample consists of, the experimental class, which received instruction using Virtual Reality-based learning, and the control class, which used the discussion method. The research instrument was an essay test designed to measure students’ critical thinking skills based on the following indicators: analysis, evaluation, inference, and argument assessment. Data analysis was conducted using the Independent Sample t-Test with the help of SPSS software.The results showed a significant difference in critical thinking skills between the experimental and control classes. This is evidenced by the one-tailed significance value of 0.000 < 0.05, which indicates that the Virtual Reality learning method has a positive effect on improving students’ critical thinking skills. Therefore, the application of Virtual Reality technology in Islamic Religious Education can be a strategic alternative to foster 21st-century thinking skills.